2010
DOI: 10.3109/13693786.2010.486412
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of low molecular weight chitosan against clinical isolates ofCandidaspp.

Abstract: Chitosan is a natural polymer derived from chitin, a structural component of fungi, insects and shrimp, which exerts antimicrobial effects against bacteria and fungi. The aim of this study was to investigate the in vitro antifungal activity of low molecular weight chitosan (LMWC), and the potential synergy between chitosan and a currently used antifungal drug, fluconazole. The in vitro minimal inhibitory concentrations (MICs) of chitosan and fluconazole against 105 clinical Candida isolates were measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…In contrast, higher minimum inhibitory concentrations (MIC) have been reported at pH 7.0 for 70-kDa-MW chitosan than at pH 4.0. 30 This may be because of the poorer solubility of most chitosan at neutral pH. Thus, likely because of its water solubility, HMWC is effective at neutral pH and is suitable for oral applications where a neutral environment is more favorable for oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, higher minimum inhibitory concentrations (MIC) have been reported at pH 7.0 for 70-kDa-MW chitosan than at pH 4.0. 30 This may be because of the poorer solubility of most chitosan at neutral pH. Thus, likely because of its water solubility, HMWC is effective at neutral pH and is suitable for oral applications where a neutral environment is more favorable for oral health.…”
Section: Discussionmentioning
confidence: 99%
“…16,25 Many chitosan derivatives exist, and their properties and antimicrobial activity vary with the molecular weight, degree of deacetylation, pH, and other factors. [26][27][28][29][30] Therefore, several chitosan derivatives with different chemical characteristics should be examined to determine those suitable for each application.…”
mentioning
confidence: 99%
“…Work by other investigators has shown that chitosan has antimicrobial activities against various pathogens including bacteria, fungi and viruses, suggesting a broad antimicrobial spectrum (Alburquenque et al, 2010; El-Sharif and Hussain, 2011; Jayakumar et al, 2011; Potara et al, 2011; Tayel et al, 2010). Despite distinctive differences between gram-negative and gram-positive bacteria, an antibacterial agent’s first interaction with its target will be at the cell surface, compromising either the cell wall or outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan's antifungal activity has been reported in a variety of fungi [22,[36][37][38][39][40]. The literature does not reveal general trends in fungal inhibition with regard to chitosan's characteristics.…”
Section: Chitosan As An Antimicrobial Agentmentioning
confidence: 90%